Utilization of Invasive Procedures for Adult Eustachian Tube Dysfunction. (November 2020) - McCoul, Edward D.; Weinreich, Heather M.; Mulder, Hillary; Man, Li-Xing; Schulz, Kristine; Shin, Jennifer J.
Objective: Eustachian tube dysfunction (ETD) is a common diagnosis among adults presenting for outpatient care. We sought to determine national utilization and the associated cost of invasive procedures for adult ETD. Study Design: Cross-sectional study. Setting: National health care database. Subjects and Methods: The Truven Health MarketScan Databases (2010-2014) analytic cohort included health care encounters of patients ≥18 years of age with a diagnosis of ETD or related conditions of otitis media with effusion (OME) or tympanic membrane retraction (TMR). Visits associated with recent diagnoses of acute upper respiratory infection, head and neck cancer, or radiation therapy were excluded. Invasive procedure usage was subdivided into nasal and otologic procedures. Results: ETD, OME, or TMR was diagnosed in 1, 298, 987 patients, 11.1% of which were chronic. The most common procedure was diagnostic endoscopy (including nasal endoscopy and laryngopharyngoscopy), which was used most frequently in the first 3 months after diagnosis, during which it was performed in 120, 971 (9.3%) patients. The most frequent therapeutic nasal procedure was eustachian tube inflation without catheterization, performed in 11, 412 patients over 5 years at a total cost of $1, 210, 939 ($106 per person annually). The most common therapeutic otologic procedure was myringotomy with tympanostomy, performed on 56, 137 patients over 5 years at a total cost of $47, 713, 708 ($810 per person annually). Conclusion: Several nasal and otologic procedures are associated with a diagnosis of adult ETD at substantial cost. Development of therapeutic alternatives should be sought to mitigate the need for invasive procedures to treat this condition.